THE EFFECT OF ALOE VERA GEL EDIBLE COATING AND GLYCEROL ON THE PHYSICOCHEMICAL CHARACTERISTICS OF RED GRAPES (Vitis vinifera L.) - Irna Dwi Destiana; Zulfa Nur Anisa; Nurul Mukminah (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2021)
Red grape (Vitis vinifera L.) is easy to get perishable and wrinkles/wilt, brown in color, and soft fruit flesh. one of the benefits of edible coating is that it can protect products from microbiological damage. The ability of aloe vera as an antimicrobial can be a potential ingredient for making edible coatings,. Besides, the use of aloe vera as an edible coating is also very easy and affordable (cheap). The purposes of this study are to determine the effect of glycerol addition and the best treatment of aloe vera edible coating on the quality of the red grape. The experiment used a completely randomized design (CRD) as an experimental design with 4 treatment factors, namely the concentration of glycerol (P1=0%, P2=3%, P3=5%, P4=7%). Each concentration was repeated three times. The parameters observed were physicochemical characteristics (weight reduction, pH, total titrated acid), hedonic quality test (color, aroma, texture). The results showed that the treatment of 3% glycerol was the best treatment since it could maintain the condition of the fruit well during storage, especially weight reduction, aromas, and textures. Parameters that highly affect the quality of red grapes are texture and weight loss.